N-heterocyclic carbene-catalyzed cascade reaction involving the hydroacylation of unactivated alkynes - Biju, Akkattu T.; Wurz, Nathalie E.; Glorius, Frank (Journal of the American Chemical Society, 2010)
The N-heterocyclic carbene (NHC)-catalyzed hydroacylation of unactivated alkynes to provide α,β-unsaturated ketones is reported. In addition, a rare case of an efficient and selective dually NHC-catalyzed cascade reaction involving the hydroacylation of alkynes and a subsequent intermolecular Stetter reaction allows the formation of chromanones containing a 1,4-diketone moiety.

N-Heterocyclic carbene catalyzed umpolung of michael acceptors for intermolecular reactions - Biju, Akkattu T.; Padmanaban, Mohan; Wurz, Nathalie E.; Glorius, Frank (Angewandte Chemie-International Edition, 2011)
eahciM! The N-heterocyclic carbene catalyzed umpolung of Michael acceptors proceeds through the formation of a deoxy-Breslow intermediate (see scheme; EWG=electron-withdrawing group). This nucleophilic species can react with other Michael acceptors in an intermolecular fashion, thereby resulting in the formation of homo- or heterodimeric olefins. This “Michael umpolung” should become a valuable method for the formation of densely functionalized olefins.
Keywords: carbenes; Michael acceptors; nitrogen heterocycles; organocatalysis; umpolung